Evaluation of the biochemical methane potential of pig manure, organic fraction of municipal solid waste and cocoa industry residues in Colombia (2017)
Colombia is a country with national policies, in order to manage, direct and guide necessary actions to treat solid waste and reduce the negative environmental impacts that these generated after their disposition. These policies are consistent with international guidelines, and it is from them that efforts are made to reduce world consumption of primary energy, thus generating interest in the potential use of biomass as a source alternative energy. The biochemical methane potential (BMP) is a test used to characterize the raw materials in trials related to the optimization of anaerobic digestion and co-digestion; it allows to find the type of substrate and co-substrate with the greatest methane potential production. This study focuses on the evaluation of the production of methane through the anaerobic process of digestion and co-digestion using three different available substrates in Colombia, of which there is very few information on the methane production potential (cocoa shell and pods), along with other common waste (organic fraction of municipal solid waste and pig manure). This evaluation was realized applying the BMP test to each individual substrate and six mixtures of these substrates; anaerobic processes of digestion and co-digestion were carried out, by testing with batch reactors of 250 mL, in mesophilic conditions (32°C - 36°C), obtaining the BMP of each substrate and of the mixtures. To these residues, a physical-chemical characterization was realized prior the BMP test, which was determined: values of solid volatile, total solids, organic matter and nitrogen Kjeldahl. With the obtained characterization six mixtures were prepared to evaluate: three with carbon/nitrogen (C/N) relation of 25 and three with C/N relation equal to 35. Methanation potential was also evaluated in three levels of volatile solids grams (gVs):0.5, 1 and 2. The three residues evaluated (pig manure, cocoa shell and pods, and organic fraction of municipal solid waste) have the ability to be used for the production of methane. In the trial of BMP, the pig manure was the higher methane production with 437.33 mL CH4/gVs, followed by organic fraction of municipal solid waste with a generation of 377.25 mL CH4/gVs. The test results of anaerobic codigestion indicate that the best mix in terms of biogas production is the Mixture1, with 25 C/N relation and 0.5 gVs, which allows inferring optimal condition at the start of the experiment. This mixture reports a production of methane 2,485.91 mL CH4/gVs. The results obtained in the different tests allow visualizing that the application of this methodology serves as a valuation of the solid residues that cause a negative impact on the environment. © Copyright 2017, AIDIC Servizi S.r.l.